How does teacher-perceived principal leadership affect teacher self-efficacy between different teaching experiences through collaboration in China? A multilevel structural equation model analysis based on threshold - Xie, Zhiyong; Wu, Rongxiu; Liu, Hongyun; Liu, Jian (Frontiers in Psychology, 2022)
Teacher self-efficacy is one critical factor impacting students’ learning outcomes. Literature have indicated that teacher-perceived principal leadership, teacher collaboration, and teaching experience greatly affect teacher self-efficacy. However, little is known about the mechanisms behind the relationship. This study examined whether teacher collaboration mediated the relationship between teacher-perceived principal leadership and teacher self-efficacy, and the moderating role of teaching experience in the mediating process. With an analysis of 14,121 middle school teachers in China, this study first confirmed the statistically positive role that teacher-perceived principal leadership played in teacher self-efficacy. Furthermore, it revealed the mediation role of teacher collaboration in the relationship and the mediated path was moderated by teaching experience. In the end, it also uncovered the existence of threshold in teaching experience linking the relationship between the teacher-perceived leadership with teacher self-efficacy, and the threshold was approximately at teachers’ third year of teaching. The relationship between the teacher-perceived leadership with teacher self-efficacy was much stronger when teaching experience was below the threshold while decreasing when teaching experience was above the threshold. This study highlighted the mediating and moderating mechanisms linking teacher-perceived principal leadership and teacher self-efficacy, which had theoretical and practical implications for intervention and improvement of teacher self-efficacy.